2020
DOI: 10.1093/ajhp/zxaa387
|View full text |Cite
|
Sign up to set email alerts
|

Preparing pharmacists to increase naloxone dispensing within community pharmacies under the Pennsylvania standing order

Abstract: Purpose Opioid misuse and overdose deaths remain a public health concern in the United States. Pennsylvania has one of the highest rates of opioid overdose deaths in the country, with Philadelphia County’s being 3 times higher than the national average. Despite several multimodal interventions, including use of SBIRT (screening, brief intervention, and referral to treatment) methods and naloxone distribution, the rate of overdose deaths remains high. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 42 publications
0
36
1
Order By: Relevance
“…Stigma has been identified as a contributing factor to reduced access to harm reduction programs [ 23 ]. Almost half of the pharmacists in this survey indicated that they did not want to attract customers with SUD to their pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma has been identified as a contributing factor to reduced access to harm reduction programs [ 23 ]. Almost half of the pharmacists in this survey indicated that they did not want to attract customers with SUD to their pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…20 Training on naloxone counseling for community pharmacists resulted in a reduction in stigmatizing attitudes and an increase in pharmacistreported con dence to appropriately identify, discuss, and dispense naloxone. 21 Pharmacist trainings should be created regarding FTS counseling, similar to trainings regarding naloxone counseling in an effort to increase pharmacist comfort and con dence in FTS distribution.…”
Section: Discussionmentioning
confidence: 99%
“…OEND training is not standardized and is, therefore, highly variable (Razaghizad et al., 2021). Policemen and women, pharmacists, fire fighters, and other people in health occupations typically have been trained in OEND to diagnose an overdose and respond accordingly (Ray et al., 2015; Santa et al., 2021; Winograd et al., 2017). However, often, by the time someone who has received OEND training is logistically able to administer care to someone who has overdosed, a bystander has already begun the rescue attempt.…”
Section: Oend Training In the Service Industrymentioning
confidence: 99%